Peran ASI Eksklusif dan Makanan Pendamping ASI dalam Pencegahan Stunting - Salsabillah, Wishal; Doriana Pasaribu, Rina; Aritonang, Anggy Putri M; Sagala, Chintya Nurmareti; Sihombing, Deasy Octavia; Amanda, Fahira; Saruksuk, Hotriani Rahayu (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2025)
Stunting in toddlers is a serious nutritional problem that has a negative impact on children's growth and development. The effects include cognitive disorders in the brain, stunted bone growth, atrophy of the muscular system, anemia, digestive problems, recurrent infections, and underweight conditions. Long-term impacts on non-communicable diseases in the future. In the accompanying factors of inadequate breast milk due to low micronutrient-containing foods, types of food that are not diverse, insufficient amounts of food and food contaminated with bacteria. This study aims to analyze the relationship between exclusive breastfeeding and complementary foods (MP-ASI) with the incidence of stunting. The method used is a cross-sectional design, where data were collected through questionnaires. The results show that stunting, which is a physical growth disorder due to nutritional imbalance, is influenced by inadequate breastfeeding practices and inappropriate diets. The prevalence of stunting in Indonesia ranks high in Asia, with the main causal factors including family nutrition knowledge, sanitation, and social support. This study concludes that exclusive breastfeeding is significantly associated with a decrease in the incidence of stunting, while MP-ASI shows a less consistent effect. Therefore, increasing education regarding the importance of exclusive breastfeeding and appropriate complementary feeding is very necessary to prevent stunting in toddlers.